Distribusi Pendapatan Masyarakat Nelayan Pajaele Berdasarkan Ekonomi Islam - Rusnaena; Wijaya, Adi Wijaya; Zubair, Muhammad Kamal; Wahyu, Andi Rio Makkulau (Program Studi Ekonomi Syariah IAIN Parepare, 2022)
This research paper investigates the income distribution practices and conducts an Islamic economic analysis within the Pajalele Fishermen's Community. The study aims to explore how assets, whether privately or publicly owned, are fairly distributed to deserving recipients in alignment with Islamic economic principles, ultimately promoting societal welfare. A qualitative descriptive approach was adopted, and data was gathered through observations, interviews, and documentation. Data analysis involved data reduction, data presentation, and data verification. The research findings reveal several key insights: First, the income distribution mechanism within the Pajalele Fishermen's Community involves the sale of fish to meet daily needs, with catches being distributed to markets in the Lembang area. Moreover, fishing communities' income sources are diversified beyond marine products, encompassing other business activities. Second, the Islamic economic analysis highlights that while income distribution partially adheres to Islamic principles, there are certain aspects, particularly income derived from selling fish, that may not fully align with these principles. Nevertheless, the distribution activities demonstrate an altruistic approach and prioritize the welfare of others. Third, the mechanism of fisherman's catch distribution involves the cooperation of small boat fishermen, who pass on the catch from big boat fishermen to collectors, facilitating further distribution to fish sellers operating in the Lembang area.